Eremophilane-type and xanthanolide-type sesquiterpenes from the aerial parts of Xanthium sibiricum and their anti-inflammatory activities. (April 2023) - Wang, Jingwen; Wang, Dongsheng; Feng, Li; Li, Xin; Gong, Yuanxiang; Wang, Zhe; Tan, Ninghua; Han, Jing
Abstract: The traditional Chinese medicine Xanthium sibiricum Patrin ex Widder is used to treat wind-cold headache, nasal congestion, nasal discharge, allergic rhinitis, sinusitis, urticaria, and arthritis. Our previous studies found that sesquiterpene lactones, the main bioactive constituents of X. sibiricum, relieved airway inflammation in an asthma mouse model. To obtain active sesquiterpenes, five undescribed ones, including a pair of eremophilanes and three xanthanolides, together with eight known xanthanolides were isolated from X. sibiricum . Their structures were identified by IR, UV, HR-ESI-MS and NMR spectroscopic data, and their absolute configurations were determined by X-ray crystallographic diffraction analysis and the comparison between their experimental and calculated electronic circular dichroism. All isolated compounds were evaluated for their inhibitory effects on nitric oxide production, and Tnf-α, Il-1β, and Il-6 mRNA expression induced by lipopolysaccharide in the macrophage cell line RAW264.7. Further investigation showed that xanthsibiriolide and 11 β -hydroxyl-13-chloro-8- epi -xanthatin exerted their anti-inflammatory effects by inhibiting the PI3K/AKT/mTOR signaling pathway. Analysis of the structure-activity relationships indicated that the α, β -unsaturated lactone ring and the 1, 5-epoxide group might be the bioactive groups of xanthanolides, and these results provide a basis for further exploration of sesquiterpene-type lead compounds with anti-inflammatory activity. Graphical abstract: Five undescribed sesquiterpenes, including a pair of eremophilane-type sesquiterpenoid epimers and three xanthanolide-type sesquiterpenoids, together with eight known xanthanolide sesquiterpenoids were isolated from Xanthium sibiricum Patrin ex Widder. All the isolated sesquiterpenes were evaluated for their anti-inflammatory activities. Image 1 Highlights: Five undescribed sesquiterpenes were isolated from Xanthium sibiricum Patrin ex Widder. Their structures were determined based on NMR, X-ray diffraction, and calculated ECD. All isolated compounds were evaluated for their anti-inflammatory activities. The α, β -unsaturated lactone ring and 1, 5-epoxide group maybe bioactive groups of xanthanolides.